Epidemiologia da ferrugem do cafeeiro conilon em diferentes estratos de altitude - Camara, Guilherme de Resende (2019)
Brazil is a world leader in coffee production and export. The occurrence of diseases in the Conilon coffee tree is one of the limiting barriers to increase coffee production and productivity. Knowledge of environmental conditions allows the planning and evaluation of strategies for phytosanitary management, which minimize damage and loss, promoting socio-economic-environmental development. In this context, it is necessary to develop technologies for phytosanitary management that consider the environmental effects on the occurrence and intensity of the Conilon coffee rust, helping in the decision making and rational elaboration of phytosanitary management for this disease. The objective of this study was to evaluate the effect of altitude, temperature, relative humidity and rainfall on the intensity (incidence and severity) of Conilon coffee rust. There was a difference in the temporal distribution pattern of the disease in the different altitude strata (AE). The higher the altitude stratum, the lower the disease progression rate and the lower daily favorability for H. vastatrix infection in conilon coffee. For the variable incidence of coffee rust, the Gompertz model was the best fit to describe the epidemic. There was a correlation between the epidemiological variables in the different AE and the meteorological variables.